Effect of sodium bicarbonate and sodium bentonite on digestion and ruminal fermentation of forage sorghum silage-based rations fed to growing steers - Jacques, K.; Axe, D.; Harris, T.; Harmon, D.; Bolsen, K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One percent sodium bicarbonate increased intake of a 50% silage-50% grain ration, but had no effect on intake of an 84% sorghum silage ration. Adding concentrate (rolled sorghum grain) lowered rumen pH slightly and decreased acid detergent fiber and starch digestion. The bicarbonate had no effect on digestibility, but 2% bentonite lowered digestibility of neutral and acid detergent fiber. Neither compound affected ruminal fermentation characteristics.
Keywords: Beef; Sodium bicarbonate; Sodium bentonite; Digestion; Ruminal fermentation; Sorghum silage